Design and Implementation of a UWB-Based Distance Information Provisioning System for Urban Transit - Han, Jonghun; Han, Min Ho; Kim, Jinsu; Ko, Young Bae (Journal of Korean Institute of Communications and Information Sciences, 2024)
This study presents a development of a UWB-based distance information provisioning system for use in challenging GPS-denied environments, such as metro or urban transit systems. The primary objective of this system is to enhance the reliability of UWB communication and transmit real-time distance values between trains and surrounding anchors to a central server. To achieve this goal, the system incorporates SS-TWR scheduling and ranging scheduling, significantly improving system stability. Experimental validation conducted in a scaled-down urban transit environment demonstrates the high reliability of the developed system. The results of this research are expected to expand the potential applications of train location-based services in the environments comprised of underground tunnels, providing a foundation for practical implementation.
Keywords: Ranging; Train; Urban Transit; UWB